Traduire l’Ekphrasis. Le cas des Fleurs du mal de Baudelaire en Iran - Habibifar, Elnaz (Studia Romanica Posnaniensia, 2021)
Cultural exchanges between Iran and France started over three centuries ago. In spite of the strong relationship between the two countries, some books such as Les Fleurs du mal (Flowers of Evil) went unnoticed in Iranian society. In addition to the literary value of the book, we propose to study ekphrasis in Baudelaire’s poems and its translation into Persian. Its meaning being that of a general description an artwork (imaginary or real), the term ekphrasis belongs to an interdisciplinary field of literature and art where the textual challenges we face may vary from one to another. To narrow down our study, we will focus on four chosen poems that have a minimum of two published translations in Persian, thus allowing the opportunity for a comparative study. These chosen poems, “La Beauté”, “L’Invitation au voyage”, “Les Plaintes d’un Icare” and “Femmes damnées” (“Delphine et Hippolyte”) as well as our corpus translation in Persian, are being studied and analysed through Descriptive Translation Studies. The analysis focuses on the ekphrastic aspect of these poems, their translations into Persian through syntactic and semantic levels and the influence of culture and society on the translation.